Current state and prospects for digitalization of the Russian coal industry - Yu. P. Panov; A. A. Grabsky; A. A. Rozhkov (Известия высших учебных заведений: Геология и разведка, 2023)
Background. Innovative robotic systems for mineral extraction and processing are increasingly changing the core operational principles of mining enterprises, thus making the creation of an intelligent mining enterprise a reality.Aim. To develop a set of proposals for promoting the digitalization of the coal industry in Russia by carrying out an analysis of the current state of implementation of innovative equipment and digital technologies within the Industry 4.0 state initiative in Russian coal companies.Materials and methods. The research was conducted using the methods of systems approach, value chain theory, expert evaluation, technological foresight, logical and comparative analysis, economic and statistical processing of information, including its tabular interpretation. The research materials included the data of coal companies, JSC “Rosinformugol”, Internet sources, and open publications.Results. The proposal is made to develop five groups of key technological digital industry platforms(TP), as follows: 1) TP “Prospecting and exploration works”; 2) TP “Underground mining technologies”; 3) TP “Open-pit mining technologies”; 4) TP “Technologies for processing coal and industrial waste”; 5) TP “Technologies for transporting rock mass”. It is proposed to implement the innovative digital potential of the coal industry in two stages, thereby completing the structural and digital transformation of the coal industry.Conclusion. The proposed TPs of the Russian coal industry should solve the following tasks:determination of the basic requirements and functional properties of the Russian coal industry based on the Industry 4.0 state initiative, along with the principles of their implementation;determination of the main technological directions for the main sectors (processes) of technological development of the coal industry, including prospecting and exploration; underground and open-pit coal mining; upgrading and processing of coal and industrial waste; transportation of coal;identification of the main components, technologies, information and management solutions in all the above processes;diversification of the activities of coal mining companies in the creation of products with high added value;overcoming the technological gap and import dependence by implementing phased import substitution and innovative development of the Russian coal industry and mining engineering with the achievement of technological sovereignty.The research results can be used when creating a unified network of scientific and educational centers on the principles of public-private partnership for the development and industrial implementation of innovative technologies in the coal, mining, and exploration industries, as well as in the training of highly-qualified personnel on the basis of Sergo Ordzhonikidze Russian State University for Geological Prospecting.